2020
DOI: 10.1038/s41419-020-2477-1
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the autophagy modulator Dram1 exacerbates pyroptotic cell death of Mycobacteria-infected macrophages

Abstract: DNA damage regulated autophagy modulator 1 (DRAM1) is a stress-inducible regulator of autophagy and cell death. DRAM1 has been implicated in cancer, myocardial infarction, and infectious diseases, but the molecular and cellular functions of this transmembrane protein remain poorly understood. Previously, we have proposed DRAM1 as a host resistance factor for tuberculosis (TB) and a potential target for host-directed anti-infective therapies. In this study, we generated a zebrafish dram1 mutant and investigated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…When host cells detect pathogenic mycobacteria that cause tuberculosis, DRAM1 expression is activated downstream of the immunity regulating transcription factor NFκB (van der Vaart et al, 2014). Knockdown or knockout of dram1 increased susceptibility to mycobacterial infection in zebrafish, identifying Dram1 as a host resistance factor (van der Vaart et al, 2014;Zhang et al, 2020). In support of this finding, overexpression of dram1 was protective against mycobacterial infection by enhancing autophagic defences against intracellular bacteria and stimulating vesicle fusion events with lysosomes (van der Vaart et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…When host cells detect pathogenic mycobacteria that cause tuberculosis, DRAM1 expression is activated downstream of the immunity regulating transcription factor NFκB (van der Vaart et al, 2014). Knockdown or knockout of dram1 increased susceptibility to mycobacterial infection in zebrafish, identifying Dram1 as a host resistance factor (van der Vaart et al, 2014;Zhang et al, 2020). In support of this finding, overexpression of dram1 was protective against mycobacterial infection by enhancing autophagic defences against intracellular bacteria and stimulating vesicle fusion events with lysosomes (van der Vaart et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…This role of Dram1 is important in defence against mycobacterial infection in the zebrafish model for tuberculosis, and mammalian DRAM1 was found to associate with Mycobacterium tuberculosis phagocytosed by primary human macrophages (van der Vaart et al, 2014). Furthermore, we recently described how zebrafish macrophages lacking Dram1 failed to deliver pathogenic mycobacteria to acidic endolysosomal compartments, ultimately resulting in an inflammatory type of cell death -called pyroptosis -which disseminates the infection (Zhang et al, 2020). Besides its function in vesicle trafficking, DRAM1 is required for apoptosis mediated by the tumour suppressor p53 in relation to cancer and in HIV infected CD4(+) T cells (Crighton et al, 2006;Laforge et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…DRAM1 is a stress-induced regulator of autophagy and cell death associated with cancer, myocardial infarction, and infectious disease. 42 Its acts as a tumor inhibitor in non-small-cell lung carcinoma (NSCLC) by promoting epidermal growth factor receptor (EGFR) lysosome degradation and regulates autophagy as well as cell proliferation by inhibiting the phosphatidylinositol 3-kinase-Akt-mechanistic target of rapamycin (mTOR)-ribosomal protein S6 pathway. 43 , 44 It has been reported that DNER promotes the epithelial-to-mesenchymal transition in breast cancer through the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DRAM1 functions through autophagic targeting and phagosomal maturation of M. marinum , thereby restricting bacteria during the early phase of infection. Dissemination of M. marinum infection is associated with defective autophagy and gasdermin Eb-mediated pyroptotic cell death in dram1 mutant zebrafish larvae ( 82 ). However, it remains to be characterized whether DRAM1 plays a crucial role in host defense to other NTM strains through activation of autophagy and prevention of cell death.…”
Section: Autophagy In Ntm Infectionsmentioning
confidence: 99%